Uncovered workers in plants covered by collective bargaining: Who are they and how do they fare? - Boris Hirsch; Philipp Lentge; Claus Schnabel (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2022)
In Germany, employers used to pay union members and non-members in a plant the same union wage in order to prevent workers from joining unions. Using recent administrative data, we investigate which workers in firms covered by collective bargaining agreements still individually benefit from these union agreements, which workers are not covered anymore, and what this means for their wages. We show that about 9 percent of workers in plants with collective agreements do not enjoy individual coverage (and thus the union wage) anymore. Econometric analyses with unconditional quantile regressions and firm-fixed-effects estimations demonstrate that not being individually covered by a collective agreement has serious wage implications for most workers. Low-wage non-union workers and those at low hierarchy levels particularly suffer since employers abstain from extending union wages to them in order to pay lower wages. This jeopardizes unions' goal of protecting all disadvantaged workers. – – In Deutschland zahlen Arbeitgeber traditionell den gleichen Tariflohn für Gewerkschaftsmitglieder und -nichtmitglieder im selben Betrieb, um letztere von einem Gewerkschaftsbeitritt abzuhalten. Mit aktuellen Daten aus der Verdienststrukturerhebung untersuchen wir, welche Arbeitnehmer in tarifgebundenen Betrieben heute noch individuell von tariflich vereinbarten Gewerkschaftslöhnen profitieren, welche Arbeitnehmer davon nicht mehr abgedeckt werden, und was dies für deren Entlohnung bedeutet. Wir zeigen, dass ungefähr 9 Prozent der Arbeitskräfte in tarifgebundenen Betrieben keine individuelle Abdeckung (und damit keinen Gewerkschaftslohn) mehr erfahren. Ökonometrische Analysen mit unbedingten Quantilsregressionen und Firmenfixe-Effekte-Schätzungen machen deutlich, dass das Fehlen einer individuellen Abdeckung durch Tarifverträge für die meisten Arbeitskräfte substanzielle Auswirkungen auf ihre Entlohnung hat. Nicht gewerkschaftlich organisierte Niedriglöhner und solche auf unteren Hierarchieebenen leiden besonders, weil ihre Arbeitgeber davon absehen, die Tariflöhne auf sie anzuwenden, um geringere Löhne zahlen zu können. Dieses Vorgehen gefährdet das gewerkschaftliche Ziel, alle benachteiligten Arbeitskräfte zu schützen.
Keywords: J31; J53; 330; collective bargaining; union wage; uncovered workers; Germany